Attitude, sports participation and academic performance of undergraduate student-athletes in Saudi Arabia - Alahmed, Mustafa; Yusof, Aminuddin; Shah, Parilah (University of Pitesti, Romania, 2016)
Many studies have reported inconsistent results on the relationship between competitive sports participation and academic achievement. Attitude was not studied in previous research on competitive sport participation and in Saudi Arabia, the attitude towards sports participation is low among students due to the fear of negative influence of sport on academic achievement. This study examines whether attitude towards sports participation might play a role in mediating the relationship between sports participation and academic achievement. A total of 102 undergraduate student-athletes from three universities in Saudi Arabia were selected as the sample of this study. Results showed there is a significant relationship between competitive sports participation and academic performance, mediated by the attitude towards competitive sports participation. This study found that the higher the subjects' participation in competitive sports, the higher their academic performance, especially when they exhibit positive attitude towards their participation in competitive sports.